Assessment of the prognostic value of preoperative high-sensitive troponin T for myocardial injury and long-term mortality for groups at high risk for cardiovascular events following noncardiac surgery: a retrospective cohort study - Zhu, Yingchao; Bi, Yaodan; Yu, Qian; Liu, Bin (Frontiers in Medicine, 2023)
Abstract Background Few studies explored the association between high-sensitive cardiac troponin T (hs-cTnT) and long-term mortality for patients after surgery. This study was conducted to assess the association of hs-cTnT with long-term mortality and to investigate the extent to which this association is mediated via myocardial injury after noncardiac surgery (MINS). Methods This retrospective cohort study included all patients with hs-TnT measurements who underwent non-cardiac surgery at Sichuan University West China Hospital. Data were collected from February 2018 and November 2020, with follow-up through February 2022. The primary outcome was all-cause mortality within one year. As secondary outcomes, MINS, length of hospital stay (LOS), and ICU admission were analyzed. Results The cohort included 7156 patients (4299 [60.1%] men; 61.0 [49.0-71.0] years). Among 7156 patients, there were 2151(30.05%) with elevated hs-cTnT(>14 ng/L). After more than one year of follow-up, more than 91.8% of mortality information was available. During one-year follow-up after surgery, there were 308 deaths (14.8%) with a preoperative hs-cTnT >14 ng/L, compared with 192 deaths (3.9%) with a preoperative hs-cTnT <=14 ng/L(adjusted hazard ratio [aHR] 1.93, 95% CI 1.58-2.36; P< .001). Elevated preoperative hs-TnT was also associated with several other adverse outcomes(MINS: adjusted odds ratio[aOR] 3.01; 95% CI, 2.46-3.69; P < .001; LOS: aOR 1.48, 95%CI 1.34-1.641; P < .001; ICU admission: aOR 1.52, 95%CI 1.31-1.76; P < .001). MINS explained approximately 33.6% of the variance in mortality due to preoperative hs-cTnT levels. Conclusions Preoperative elevated hs-cTnT concentrations have a significant association with long-term mortality after noncardiac surgery, one-third of which may by accounted for by MINS.